POLITIK PLURALISME HUKUM DALAM HUKUM UNDANG-UNDANG KEKUASAAN KEHAKIMAN : KAJIAN TERHADAP PENGAKUAN HUKUM TIDAK TERTULIS DALAM UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - Jamin, Mohammad (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractIt is empirical fact in Indonesia not only has written law which imposed by state power ( state law). Beside written law there is also unwritten law which often called the non state law. Political of law to uniting as one political unity and enforce the legal sentralism has disregarded the fact of legal pluralism ( the political of ignorance). Political of law of the Judicial Power Code which imposed during the time does not clearly arrange the state recognation to unwritten law, even unwritten law is recognnized, but still very sumir and floating. Although Code No. 48/2009 about Judicial Power adopt the politics of legal pluralism and recognizes the existence unwritten law, but it is still sham (weak legal pluralism), causing that in fact predominate the state law still happened and unwritten law only becoming complement to state law. Political forwards legal pluralism in Judicial Power Code ideally is not made conditional. The political legal pluralism of Judicial Power Code must to adopt strong legal pluralism, so can accommodate pluralism in society.